Karakteristik Bahan Ajar IPA Terpadu Berbasis Kontroversi - sudarto sudarto; tawil tawil (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
Integrated science learning is the latest science learning icon and is recommended in the national curriculum at all levels of education. Integrated learning is essentially a learning that allows students both individually and in groups to actively seek, explore / explore, and find concepts and principles holistically and authentically. Science as a subject should be taught in its entirety between the study of Physics, Chemistry, and Biology. Facts on the ground show that science learning so far in various levels of education is generally not integrated. The ongoing learning process still indicates the presence of Physics, Chemistry, and Biology subjects. This happens because of various things, including the absence of representative integrated science teaching materials. Subjects or respondents in this study were students of the Natural Sciences Study Program FMIPA UNM 2014 Class Regular Class. The number of respondents was 28 people. This research was conducted in Odd semester 2016/2017 academic year. This research is classified as development research. The results of this study in the form of the characteristics of integrated science teaching materials based on controversy that has been developed which includes: contains a title that is controversial; arranged with integrated, integrated, and shared integration; arranged with a principle that in preparing the teaching material always involves physical, chemical, and psychological material; unique and creative; its contents are easy to understand like reading a short story; fun to read; open mind; the title of the material is intriguing; as if the material in teaching materials is human-like character; can increase creativity; the title of the material attracts attention; the contents are interesting; the language used is beautiful and unique; can come up with creative ideas; not boring; and increase imagination and thinking ability.